2015
DOI: 10.3329/ajmbr.v1i2.25628
|View full text |Cite
|
Sign up to set email alerts
|

Aqua drugs and chemicals used in aquaculture of Zakigonj upazilla, Sylhet

Abstract: Abstract:In order to investigate present status of aqua chemicals and drugs used in various aquaculture activities in Zakigonj upazilla, Sylhet. A survey was conducted, with carp polyculture, tilapia and catfish farmers, aqua-medicine sellers, representatives of pharmaceuticals companies, from July 2014 to November 2014. Each group consisted of 25 respondents. According to the survey the most common dose of lime used by the farmers during pond preparation (62.67%) and culture period (53%) is 0.5-1 kg/40m 2 . U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 4 publications
3
33
0
Order By: Relevance
“…It showed the best result (90% recovery of fish). The relevant results were found by the study of Sharmin et al (2016); Hossain et al (2016); Monir et al (2015); Chowdhury et al (2015); Ahmed et al (2015); Hasan et al (2015) and Borty et al (2016). Scott and Warren (1964) used 2 ppm concentration of methylene blue for complete destruction of fungal hyphae within 7 days treatment.…”
Section: Discussionmentioning
confidence: 79%
“…It showed the best result (90% recovery of fish). The relevant results were found by the study of Sharmin et al (2016); Hossain et al (2016); Monir et al (2015); Chowdhury et al (2015); Ahmed et al (2015); Hasan et al (2015) and Borty et al (2016). Scott and Warren (1964) used 2 ppm concentration of methylene blue for complete destruction of fungal hyphae within 7 days treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Edgell et al, (1993) found that salt treatment at 20 ppt for 60 minutes was the best to prevent mortality amongst salmon eggs. The lists of fungal treatment medicine are also found in Chowdhury et al, (2015). Kitancharoen et al,.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentration of formalin treatment gives lower hatching and survival rate. Use of formalin in very small concentration effectively reduced fungal infection in the eggs and fry of Clarias gariepinus but it originated negatively on hatchability of the eggs and formalin is effective in treating saprolegnia [19,[34][35][36][37][38]. 5mg/L concentration treatment of malachite green showed better result (hatching rate 83.67±3.51% and survival rate 87.33±6.51%) than other two lower concentration (1mg/L and 3mg/L) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One hour treatment of malachite bath at the concentration of 4-5 mg/l proved effective for the treatment of carp eggs infected with fungi Saprolegnia sp. [36,39,40]. Malachite green can prevent fungal infection of the eggs of Cyprinus carpio and tench which have been treated prophylactic ally [41].…”
Section: Discussionmentioning
confidence: 99%